Geotechnical Evaluation of Lateritic Soil Index Properties in Ekiti State Districts, Southwestern Nigeria for Road Pavement Construction - Joshua T. AKINWAMIDE; Jacob O. EHIOROBO; Oluwayinka G. AKINWAMIDE (FUDMA Journal of Engineering and Technology, 2026)
Focusing on the three Senatorial Districts of Ekiti State, this research examines local soil properties to assess their suitability for construction and infrastructure development. The investigation starts by analysing samples from the Central District, Southern, and Northern with a sample size of 160 per district, the research utilized standard laboratory procedures to assess key physical properties. Specifically, tests were performed to evaluate moisture content, specific gravity, and grading, alongside an analysis of Atterberg limits. Based on the AASHTO classification system, the soils in the Central District were classified into four categories (A-2-4, A-2-6, A-2-7, A-7-5), while the Southern District contained eight categories (A-2-4, A-2-5, A-2-6, A-2-7, A-4, A-5, A-6, A-7-5), and the Northern District had six categories (A-2-4, A-2-5, A-2-6, A-2-7, A-6, A-7-6). Results show that while Central District soils meet the requirements for base and sub-base layers, those from the Southern and Northern Districts are more effectively utilized in sub-base and sub-grade construction. Although stabilization may be needed to enhance their performance. In conclusion, the soils of Ekiti State are generally suitable for civil engineering purposes, with the Central District offering the most reliable materials for foundational, pavement, and construction projects.